A synopsis of the Euphaeidae (Odonata: Zygoptera) of Vietnam, with descriptions of two new species of Euphaea - Phan, Quoc Toan; Kompier, Tom; Karube, Haruki; Hayashi, Fumio (Zootaxa, 2018)
23 species of Euphaeidae (Odonata: Zygoptera) are reported from Vietnam including two new species of Euphaea, E. saola Phan & Hayashi, sp. nov. and E. sanguinea Kompier & Hayashi, sp. nov., and four species not recorded previously, Bayadera continentalis Asahina, 1973, B. hyalina Selys, 1879, B. nephelopennis Davies & Yang, 1996 and Euphaea pahyapi Hämäläinen, 1985. The females of Anisopleura bipugio Hämäläinen & Karube, 2013, Bayadera serrata Davies & Yang, 1996 and Euphaea hirta Hämäläinen & Karube, 2001 are described for the first time. The mutual taxonomic status of Bayadera hyalina and B. strigata Davies & Yang, 1996 is discussed. Distribution maps of all known Vietnamese species, with detailed distribution records, are provided.